Coal-based hard carbon negative electrode material and preparation method and application thereof

By mixing the coal -based raw materials and explosives to heat and carbonize at high temperature, the coal -based hard carbon negative materials that have closed -hole structures are formed, and the problem of low sodium capacity of the existing hard carbon materials and poor circulation performance have been solved. Stable cycle performance and reduce preparation costs and process complexity.

CN119330338AActive Publication Date: 2025-01-21TSINGHUA SHENZHEN INTERNATIONAL GRADUATE SCHOOL +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411496751.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-21
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The existing hard carbon materials have low sodium storage capacity and poor circulation performance in sodium ion batteries, and the cost of adding exogenous crosslinking agents is high, the product uniformity is poor, and the process is complex, making them not suitable for large-scale production.

Method used

By mixing and heating coal-based raw materials with explosive agents to form an open pore structure, and then high-temperature carbonization to close the pore structure, a coal-based hard carbon anode material with high sodium storage capacity and good circulation performance is prepared.

Benefits of technology

It achieves efficient sodium storage and stable cycle performance of coal-based hard carbon anode materials, reduces preparation costs and process complexity, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330338A_ABST
    Figure CN119330338A_ABST
Patent Text Reader

Abstract

The invention discloses a coal-based hard carbon negative electrode material and a preparation method and application thereof.The preparation method of the coal-based hard carbon negative electrode material comprises the steps that a coal-based raw material and an explosive are mixed and heated for an explosion reaction, so that a plurality of open pore structures are formed in the surface of the coal-based raw material, and a negative electrode material precursor is obtained; and heating and carbonizing the negative electrode material precursor to close the open pore structure to form a closed pore structure, thereby obtaining the coal-based hard carbon negative electrode material. The pore structure of the coal-based hard carbon negative electrode material is regulated and controlled through an explosion method, so that the sodium storage effect and the cycle performance of the coal-based hard carbon negative electrode material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery materials, and in particular to a coal-based hard carbon negative electrode material and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries have become the first choice to replace lithium-ion batteries due to their abundant sodium resources and good low-temperature performance. However, the radius of sodium ions is larger than that of lithium ions, making graphite anodes incompatible with sodium-ion battery systems. Hard carbon materials are widely used as anode materials for sodium-ion batteries due to their advantages such as large carbon layer spacing, rich pore structure, adjustable structure, stable chemical properties and low cost.

[0003] Since hard carbon materials have low sodium storage capacity and poor cycle performance, it is necessary to regulate the structure of hard carbon materials. At present, exogenous cross-linking agents and pore-forming agents are usually introduced during the pyrolysis of hard carbon materials to achieve the purpose of structural regulation of hard carbon materials. However, there are some problems in the practical application of the above method, such as the high price of introducing exogenous cross-linking agents and the large amount of cross-linking agents added, poor uniformity of the obtained products, and complex process flow, which are not conducive to large-scale production. Summary of the invention

[0004] In view of this, in order to solve at least one of the above technical problems, an embodiment of the present application provides a method for preparing a coal-based hard carbon negative electrode material.

[0005] In addition, the embodiments of the present application also provide a coal-based hard carbon negative electrode material prepared by the aforementioned preparation method, and an electrochemical device using the coal-based hard carbon negative electrode material.

[0006] The present application provides a method for preparing a coal-based hard carbon negative electrode material, the preparation method comprising: Mixing a coal-based raw material with an explosive agent and heating them to perform an explosion reaction, so as to form a plurality of open pore structures on the surface of the coal-based raw material to obtain a negative electrode material precursor; and The negative electrode material precursor is heated and carbonized to close the open pore structure to form a closed pore structure, thereby obtaining the coal-based hard carbon negative electrode material.

[0007] In some possible embodiments, the coal-based raw material includes bituminous coal, and the bituminous coal includes at least one of long flame coal, gas coal, fat coal, coking coal, lean coal and lean coal.

[0008] In some possible embodiments, in the step of mixing and heating the coal-based raw material and the blasting agent, the heating temperature is 600° C. to 800° C., and the heating time is 1 hour to 2 hours.

[0009] In some possible embodiments, the mass ratio of the coal-based raw material to the explosive agent is 1:(0.1~1).

[0010] In some possible embodiments, in the step of heating and carbonizing the negative electrode material precursor, the carbonization temperature is 1300° C. to 1500° C., and the carbonization time is 2 h to 3 h.

[0011] In some possible embodiments, the explosive agent includes nitrates, and the nitrates include KNO 3 Mg(NO 3 ) 2 、Zn(NO 3 ) 2 and Ca(NO 3 ) 2 At least one of .

[0012] In some possible embodiments, before the step of heating and carbonizing the negative electrode material precursor, the preparation method further includes: The coal-based hard carbon negative electrode material precursor is pickled; wherein the acid in the pickling includes at least one of hydrochloric acid, nitric acid and sulfuric acid, the concentration of the acid in the pickling is 1 mol / L~6 mol / L, the solid-liquid ratio of the negative electrode material precursor to the acid in the pickling is 1:(3g / mL~5g / mL), the pickling time is 5h~10h, and the pickling temperature is 25℃~60℃.

[0013] In some possible embodiments, before the step of mixing and heating the coal-based raw material and the blasting agent, the preparation method further comprises: The coal-based raw material is crushed and dried; wherein the drying temperature is 60° C. to 110° C., and the drying time is 24 h to 48 h.

[0014] The embodiment of the present application also provides a coal-based hard carbon negative electrode material, and the coal-based hard carbon negative electrode material is prepared by the preparation method as described above.

[0015] In addition, an embodiment of the present application further provides an electrochemical device, which includes a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the negative electrode plate includes a negative electrode material, and the negative electrode material is the aforementioned coal-based hard carbon negative electrode material.

[0016] Compared with the prior art, the present application mixes and heats coal-based raw materials with explosives. The surface of the coal-based raw materials has oxygen-containing functional groups, which react with the explosives during the heating process and can instantly decompose and produce gas to generate an explosion reaction. During the gas escape process, a large number of relatively open pore structures are generated on the surface of the coal-based raw materials. Subsequently, high-temperature carbonization causes the relatively open pore structures to close, forming a closed-pore structure that is difficult for solvent molecules to enter but sodium ions can freely enter and exit. This closed-pore structure is beneficial to the sodium ion storage and electrolyte isolation of the coal-based hard carbon negative electrode material, thereby achieving efficient and stable sodium storage effect and good cycle performance of the coal-based hard carbon negative electrode material. In addition, the preparation method is simple in process and low in cost, which is beneficial to the large-scale production of coal-based hard carbon negative electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 A process flow chart of the method for preparing a coal-based hard carbon negative electrode material provided in an embodiment of the present application.

[0018] Figure 2 This is a schematic diagram of the structure of the electrochemical device provided in an embodiment of the present application.

[0019] Figure 3 This is a charge and discharge curve diagram of a battery prepared with the coal-based hard carbon negative electrode material in Example 1 of the present application.

[0020] Figure 4 This is the X-ray diffraction pattern of the coal-based hard carbon negative electrode material in Example 1 of the present application.

[0021] Figure 5 This is the nitrogen adsorption isotherm diagram of the coal-based hard carbon negative electrode material in Example 1 of the present application. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0023] One of the storage mechanisms of sodium ions inside hard carbon negative electrode materials is adsorption-pore filling, that is, during the discharge process, sodium ions are first adsorbed on the surface of carbon microcrystals. As the discharge depth increases, sodium ions continue to fill in the nano-closed pores formed by the stacking of carbon microcrystals. Therefore, increasing the closed pore content of hard carbon negative electrode materials is the key to increasing the sodium storage capacity.

[0024] See also Figure 1 As shown, the preparation method of the coal-based hard carbon negative electrode material provided in the embodiment of the present application specifically includes the following steps: Step S1, mixing the coal-based raw material and the explosive agent, heating them, and performing an explosion reaction to form a plurality of open pore structures on the surface of the coal-based raw material to obtain a negative electrode material precursor.

[0025] The explosion method is adopted, by mixing and heating the coal-based raw materials and the explosive agent. Since the surface of the coal-based raw materials has a large number of oxygen-containing functional groups, under the promotion of the explosive agent, the oxygen-containing functional groups of the coal-based raw materials decompose and produce gas, an explosion reaction occurs, and a large amount of gas is instantly generated. During the gas escape process, a large number of relatively open pore structures are formed on the surface of the coal-based raw materials, which efficiently creates pores for the coal-based raw materials, effectively improving the pore content of the coal-based raw materials, and obtaining a negative electrode material precursor with a large number of open pore structures.

[0026] Furthermore, the micro-explosion method can be used to trigger the explosion using a smaller explosion and instantaneous high-pressure gas generation, which has a higher control accuracy. It is handled in accordance with strict safety operating procedures to ensure the stability and safety of the explosive during storage, mixing and application; at the same time, specially designed equipment is used to control and guide the explosion reaction, ensuring that the equipment can withstand instantaneous high pressure, and equipped with appropriate protective measures, such as pressure release devices or safety valves, to ensure the safety of the process.

[0027] In some embodiments, the coal-based raw material may be crushed before step S1. Crushing the coal-based raw material into smaller particles can increase its surface area, and at the same time make the mixing of the coal-based raw material and the explosive more uniform, increase the contact probability between the oxygen-containing functional groups and the explosive, which helps the sufficiency and uniformity of the explosion reaction, thereby improving the efficiency of the explosion reaction, increasing the gas production and the pore content formed. The median particle size D50 of the coal-based raw material after crushing can be 3μm~10μm, further can be 3μm~5μm, and can be 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm or 10μm, etc.

[0028] In some embodiments, the coal-based raw material may be dried before step S1 to remove moisture from the coal-based raw material, which is beneficial to improving the stability and fullness of the explosion reaction. The drying temperature may be 60° C. to 110° C., and the drying time may be 24 hours to 48 hours.

[0029] In some embodiments, the coal-based raw material can be bituminous coal. The characteristics of bituminous coal are between high aromatic anthracite and low aromatic lignite. It is mainly composed of carbon, hydrogen, oxygen, sulfur and a small amount of nitrogen. Unlike the ordered microcrystalline structure of anthracite-based hard carbon, bituminous coal has both aromatic units and side chains. These structural units make the ordered / disordered phase structure of bituminous coal easier to control, and more precise control can be achieved by regulating these structural units during the explosion process. Moreover, bituminous coal also has the advantage of high oxygen content. During the heat treatment process, the more abundant oxygen-containing functional groups on the surface of bituminous coal decompose and explode to produce a large amount of gas, which is conducive to the realization of a large number of pores in the precursor of coal-based hard carbon negative electrode materials compared to other coal-based raw materials. In addition, when high-oxygen-content bituminous coal is converted into hard carbon, the carbonization process of the material can be better controlled, internal stress can be reduced, and the stability and mechanical strength of coal-based hard carbon negative electrode materials can be improved.

[0030] In some embodiments, the bituminous coal may include at least one of long flame coal, gas coal, fat coal, coking coal, lean coal, and lean coal. Different types of bituminous coal may be selected and used according to specific application requirements to optimize the performance of the coal-based hard carbon negative electrode material. By exemplarily selecting long flame coal as the bituminous coal raw material, the high volatile matter and low fixed carbon content of the long flame coal may be utilized to promote the explosion reaction and form a more porous structure.

[0031] In some embodiments, the explosive agent may include a nitrate, which may include KNO 3 Mg(NO 3 ) 2 、Zn(NO 3 ) 2 and Ca(NO 3 ) 2 At least one of the above-mentioned explosive agent can release a large amount of oxygen at high temperature, effectively increase the intensity of the explosion reaction during the heat treatment process, and promote the formation of pores in the coal-based raw material.

[0032] In some embodiments, the mass ratio of the coal-based raw material to the explosive agent can be 1: (0.1-1). The mass ratio of the coal-based raw material to the explosive agent can control the intensity and scale of the explosion reaction. Within the above range, the mass ratio is conducive to optimizing the pore structure of the negative electrode material precursor and forming enough pores that can be closed in the subsequent heating carbonization process. The mass ratio of the coal-based raw material to the explosive agent can further be 1: (0.5-1), and can be exemplarily 1: 0.1, 1: 0.2, 1: 0.5, 1: 0.8 or 1: 1, etc.

[0033] In some embodiments, the heating temperature in this step may be 600°C to 800°C, further may be 700°C to 800°C, and illustratively may be 600°C, 650°C, 700°C, 750°C or 800°C; the heating time may be 1h to 2h, further may be 1.5h to 2h, and illustratively may be 1h, 1.2h, 1.5h, 1.8h or 2h, etc. Appropriate heating conditions are conducive to the full progress of the explosion reaction, so that the oxygen-containing functional groups of the coal-based raw materials can be effectively decomposed to generate the desired pore structure.

[0034] Step S2, heating and carbonizing the negative electrode material precursor to close the open pore structure to form a closed pore structure, thereby obtaining a coal-based hard carbon negative electrode material.

[0035] By heating the negative electrode material precursor to undergo high-temperature carbonization, the carbon sheets can be rearranged to form a more stable amorphous carbon structure. This carbonization process changes the pore structure of the negative electrode material precursor, and the open pore structure in the negative electrode material precursor closes to form a closed-pore structure capable of storing sodium, thereby improving the sodium storage capacity and cycle performance of the coal-based hard carbon negative electrode material. At the same time, due to the presence of the closed-pore structure, the specific surface area of ​​the coal-based hard carbon negative electrode material is reduced, which can reduce the side reactions between the coal-based hard carbon negative electrode material and the electrolyte, thereby improving the first coulombic efficiency of the battery prepared with the coal-based hard carbon negative electrode material.

[0036] In some embodiments, the carbonization temperature may be 1300° C. to 1500° C. At the above temperature, the high temperature provides sufficient energy to facilitate the rearrangement of carbon atoms to obtain a closed-cell structure. The carbonization temperature may further be 1400° C. to 1500° C., and may be 1300° C., 1350° C., 1400° C., 1450° C., or 1500° C., etc.

[0037] In some embodiments, the carbonization time may be 2h to 3h. The length of the carbonization time affects the degree of completion of the carbonization process. By controlling the carbonization time to 2 to 3h, the carbon atoms have enough time to rearrange and form a stable closed-cell structure, thereby ensuring that the carbonization process is fully carried out. The carbonization time may further be 2.5h to 3h, and may be 2h, 2.3h, 2.5h, 2.8h or 3h, etc.

[0038] In some embodiments, the negative electrode material precursor may be pickled before step S2. Specifically, the negative electrode material precursor is pickled with an acid to remove impurities such as explosives, then washed with deionized water to neutrality, and then dried at a certain temperature to remove moisture.

[0039] In some embodiments, the acid agent may include at least one of hydrochloric acid, nitric acid, sulfuric acid, and the like.

[0040] In some embodiments, the concentration of the acid (i.e., the acid agent) in the pickling is 1 mol / L to 6 mol / L, within which impurities can be effectively removed. The concentration of the acid in the pickling can further be 3 mol / L to 5 mol / L, and can be exemplarily 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, or 6 mol / L, etc.

[0041] In some embodiments, the solid-liquid ratio of the negative electrode material precursor to the acid agent is 1: (3 g / mL to 5 g / mL), and the intensity and efficiency of the pickling are controlled to ensure effective cleaning of the negative electrode material precursor while avoiding excessive corrosion of the negative electrode material precursor. The solid-liquid ratio of the negative electrode material precursor to the acid agent can further be 1: (3 g / mL to 4 g / mL), and can be 3 g / mL, 3.5 g / mL, 4 g / mL, 4.5 g / mL or 5 g / mL, etc.

[0042] In some embodiments, the pickling time is 5 h to 10 h, and the pickling temperature is 25° C. to 60° C. The appropriate time and temperature can ensure sufficient removal of impurities while avoiding damage to the structure of the negative electrode material precursor.

[0043] Compared with the prior art, the method for preparing the coal-based hard carbon negative electrode material provided in the embodiment of the present application has the following beneficial effects: 1. Coal-based hard carbon negative electrode materials are prepared by explosion method. The coal-based raw materials and explosives are mixed and heated to produce an explosion reaction, which creates pores in the coal-based raw materials and produces a large number of open pore structures. Subsequently, high-temperature carbonization closes the pores to form a large number of closed-pore structures, which is beneficial to improving the sodium storage capacity and cycle performance of coal-based hard carbon negative electrode materials. At the same time, due to the presence of a large number of closed-pore structures, the specific surface area of ​​the coal-based hard carbon negative electrode materials is reduced, the contact between the coal-based hard carbon negative electrode materials and the electrolyte is reduced, and the occurrence of side reactions is reduced.

[0044] 2. By further controlling the mass ratio of coal-based raw materials to explosives, regulating the intensity and scale of the explosion reaction, and forming micro-explosions, it is beneficial to improve the control accuracy of the explosion reaction and regulate the closed-pore structure and specific surface area in coal-based hard carbon negative electrode materials.

[0045] 3. Using bituminous coal with a high oxygen content as the coal-based raw material and combining it with the explosion method can not only significantly improve the efficiency of the explosion reaction and generate larger and more pores, thereby improving the pore structure of coal-based hard carbon negative electrode materials, but also optimize the carbonization effect and improve the stability and mechanical strength of coal-based hard carbon negative electrode materials; in addition, bituminous coal has both aromatic units and side chains, and its aromatic units and side chains can be used to more accurately regulate the pore structure during the explosion process.

[0046] 4. This preparation method is simple, efficient, and low-cost, which is conducive to the large-scale production of coal-based hard carbon negative electrode materials and has excellent commercial prospects.

[0047] The embodiment of the present application also provides a coal-based hard carbon negative electrode material, which is prepared by the above-mentioned preparation method. Since the coal-based hard carbon negative electrode material has a large number of closed-pore structures, its sodium storage capacity and cycle performance are greatly improved; and since the coal-based hard carbon negative electrode material has a small specific surface area, the contact area between the coal-based hard carbon negative electrode material and the electrolyte is small, thereby effectively reducing the occurrence of negative electrode interface side reactions.

[0048] See also Figure 2 As shown, an embodiment of the present application also provides an electrochemical device (such as a battery), the electrochemical device 100 includes a positive electrode plate 10, a negative electrode plate 20, a separator 30 and an electrolyte 40, wherein the negative electrode plate 20 includes a negative electrode material, and the negative electrode material is the coal-based hard carbon negative electrode material as mentioned above.

[0049] The electrochemical device 100 prepared using the aforementioned coal-based hard carbon negative electrode material has significantly improved discharge capacity, long cycle stability and first coulombic efficiency because the sodium storage capacity and cycle performance of the coal-based hard carbon negative electrode material are improved while the specific surface area of ​​the coal-based hard carbon negative electrode material is reduced.

[0050] The above-mentioned coal-based hard carbon negative electrode material and its preparation method and electrochemical device are further described below through specific examples.

[0051] Example 1 Step 1: First, crush the bituminous coal block into coal powder with a median particle size of 3μm~10μm; then dry the coal powder at 110℃ for 24h; grind and mix the coal powder and the explosive agent in a mortar at a mass ratio of 1:0.2, heat at 700℃ for 2h in a tubular furnace for explosion reaction, and obtain a negative electrode material precursor.

[0052] Step 2: The negative electrode material precursor is acid-washed to remove impurities, then washed with deionized water until neutral and then dried; finally, the cleaned and dried negative electrode material precursor is heated and carbonized at 1300° C. for 3 hours to obtain a coal-based hard carbon negative electrode material.

[0053] Comparative Example 1 The specific process of the preparation process refers to Example 1. The difference from Example 1 is that only coal powder is added in step 1, and no explosive is added. The preparation method of the remaining coal-based hard carbon negative electrode materials is basically the same as that of Example 1, and will not be described in detail here.

[0054] Comparative Example 2 The specific process of the preparation process refers to Example 1. The difference from Example 1 is that the time for heating for explosion reaction in step 1 is 5 hours. The preparation method of the remaining coal-based hard carbon negative electrode materials is basically the same as that in Example 1, and will not be described in detail here.

[0055] Comparative Example 3 The specific process of the preparation process refers to Example 1. The difference from Example 1 is that the temperature of the explosion reaction in step 1 is 400°C, and the preparation method of the remaining coal-based hard carbon negative electrode materials is basically the same as that in Example 1, which will not be described in detail here.

[0056] The following tests were performed on the coal-based hard carbon negative electrode materials obtained in Example 1 and Comparative Examples 1-3.

[0057] 1. The battery prepared by using the coal-based hard carbon negative electrode material in Example 1 and Comparative Examples 1-3 was subjected to charge and discharge tests. The results are shown in Table 1.

[0058] The specific preparation steps of the battery are as follows: the coal-based hard carbon negative electrode material, the binder PVDF and the conductive agent Super P are uniformly dispersed in N-methylpyrrolidone (NMP) in a mass ratio of 93.5:5:1.5, stirred for 4 hours to make a slurry, coated on the aluminum current collector, and vacuum dried in an oven at 80°C for 36 hours to form a negative electrode sheet with a diameter of 12 mm for standby use; the sodium ion battery is assembled in a glove box. Specifically, the button battery is assembled from bottom to top in the order of negative electrode shell, shrapnel, gasket, 1mm sodium sheet, glass fiber diaphragm (Whatman C), negative electrode sheet, 0.5mm gasket, and positive electrode shell. The electrolyte is prepared by dissolving 1.5M NaPF6 in a solvent of ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:2:2, and the amount of electrolyte added is 70μL on each side of the diaphragm. Finally, the battery is compacted in a button battery sealing machine to test the battery's charge and discharge curve.

[0059] The test process of the charge and discharge curve is as follows: discharge to 0V at 0.1C, then discharge to 0V at small currents of 0.05C and 0.01C respectively, and finally charge to 1.5V at 0.1C. The nominal specific capacity is set to 300mAh / g.

[0060] As can be seen from Table 1, the reversible specific capacity of the battery made of the coal-based hard carbon negative electrode material in Example 1 is 310 mAh / g, and the first-cycle coulomb efficiency is 86%. The charging specific capacity and the first-cycle coulomb efficiency are higher than those of Comparative Examples 1-3. This is because the negative electrode material prepared by the explosion method in Example 1 of the present application has a large number of closed-pore structures, so its capacity and cycle performance are greatly improved. The capacity and cycle performance of the negative electrode materials in Comparative Examples 1-3 are lower than those in Example 1, among which, since no explosive is added in Comparative Example 1, the explosion reaction is insufficient, and a large number of closed-pore structures are not effectively prepared, resulting in decreased electrical performance; the electrochemical performance of the negative electrode materials in Comparative Examples 2 and 3 also decreases due to changes in reaction conditions. The charge and discharge curves of the battery made using the coal-based hard carbon negative electrode material in Example 1 are shown in the figure. Figure 3 shown.

[0061] 2. The coal-based hard carbon negative electrode material in Example 1 was subjected to an X-ray diffraction test (XRD).

[0062] The XRD results of the coal-based hard carbon negative electrode material in Example 1 are as follows: Figure 4 As shown, the results show that the coal-based hard carbon negative electrode material obtained in Example 1 has a disordered structure, which is conducive to the embedding and extraction of sodium ions.

[0063] 3. The specific surface area of ​​the coal-based hard carbon negative electrode material in Example 1 was tested.

[0064] The specific surface area test method is as follows: 500 mg of the coal-based hard carbon negative electrode material of Example 1 is weighed and placed in a sample tube. 2 The adsorption-desorption method was used to measure the N content of the sample at different pre-set pressure points at 77K. 2 The adsorption and desorption amount was calculated to obtain the adsorption and desorption isotherm. The specific surface area was calculated from the adsorption and desorption isotherm by computer processing the data. The results are shown in Table 2.

[0065] The specific surface area test results of the coal-based hard carbon negative electrode material in Example 1 are as follows: Figure 5 As shown in Table 2 and Figure 5 The specific surface area of ​​the coal-based hard carbon negative electrode material obtained in Example 1 is 0.6 m 2 / g, which is less than that of comparative examples 1 to 3. The coal-based hard carbon negative electrode material in Example 1 has a smaller specific surface area, which is beneficial to reducing the side reaction between the electrolyte and the coal-based hard carbon negative electrode material and improving the first coulombic efficiency of the prepared battery.

[0066] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.

Claims

1. A method for preparing a coal-based hard carbon negative electrode material, characterized in that: include: The coal-based raw material and the explosive agent are mixed and heated to perform an explosion reaction, so as to form a plurality of open pore structures on the surface of the coal-based raw material to obtain a negative electrode material precursor; as well as The negative electrode material precursor is heated and carbonized to close the open pore structure to form a closed pore structure, thereby obtaining the coal-based hard carbon negative electrode material.

2. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that: The coal-based raw material includes bituminous coal, and the bituminous coal includes at least one of long flame coal, gas coal, fat coal, coking coal, lean coal and lean coal.

3. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that: In the step of mixing and heating the coal-based raw material and the blasting agent, the heating temperature is 600° C. to 800° C., and the heating time is 1 hour to 2 hours.

4. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that: The mass ratio of the coal-based raw material to the explosive agent is 1:(0.1~1).

5. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that: In the step of heating and carbonizing the negative electrode material precursor, the carbonization temperature is 1300° C. to 1500° C., and the carbonization time is 2 h to 3 h.

6. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that: The explosive agent includes nitrate, and the nitrate includes at least one of KNO3, Mg(NO3)2, Zn(NO3)2 and Ca(NO3)2.

7. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that: Before the step of heating and carbonizing the negative electrode material precursor, the preparation method further comprises: The negative electrode material precursor is pickled; wherein the acid in the pickling includes at least one of hydrochloric acid, nitric acid and sulfuric acid, the concentration of the acid in the pickling is 1 mol / L~6 mol / L, the solid-liquid ratio of the negative electrode material precursor to the acid in the pickling is 1:(3 g / mL~5 g / mL), the pickling time is 5h~10h, and the pickling temperature is 25°C~60°C.

8. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that: Before the step of mixing and heating the coal-based raw material and the blasting agent, the preparation method further comprises: crushing and drying the coal-based raw material; Wherein, the drying temperature is 60°C to 110°C, and the drying time is 24h to 48h.

9. A coal-based hard carbon negative electrode material, characterized in that: The coal-based hard carbon negative electrode material is prepared by the method for preparing the coal-based hard carbon negative electrode material according to any one of claims 1 to 8.

10. An electrochemical device, characterized in that: The electrochemical device comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet comprises a negative electrode material, and the negative electrode material is the coal-based hard carbon negative electrode material as described in claim 9.

Citation Information

Patent Citations

  • Method for preparing active carbon with developed mesopores by using coal

    CN108439399A

  • Carbon negative electrode material precursor and preparation method and application thereof, and carbon negative electrode material and preparation method and application thereof

    CN111777414A

  • Method for preparing coal-based hard carbon negative electrode material through alkali treatment modification and application

    CN115650228A

  • Porous hard carbon negative electrode material and preparation method and application thereof

    CN116404128A

  • Carbon material as well as preparation method and application thereof

    CN116675213A